Viscous placebo and carbohydrate breakfasts similarly decrease appetite and increase resistance exercise performance compared with a control breakfast in trained males. Issue 2 (16th March 2020) - Naharudin, M. N.; Adams, J.; Richardson, H.; Thomson, T.; Oxinou, C.; Marshall, C.; Clayton, D. J.; Mears, S. A.; Yusof, A.; Hulston, C. J.; James, L. J.
Abstract: Given the common view that pre-exercise nutrition/breakfast is important for performance, the present study investigated whether breakfast influences resistance exercise performance via a physiological or psychological effect. Twenty-two resistance-trained, breakfast-consuming men completed three experimental trials, consuming water-only (WAT), or semi-solid breakfasts containing 0 g/kg (PLA) or 1·5 g/kg (CHO) maltodextrin. PLA and CHO meals contained xanthan gum and low-energy flavouring (approximately 122 kJ), and subjects were told both 'contained energy'. At 2 h post-meal, subjects completed four sets of back squat and bench press to failure at 90 % ten repetition maximum. Blood samples were taken pre-meal, 45 min and 105 min post-meal to measure serum/plasma glucose, insulin, ghrelin, glucagon-like peptide-1 and peptide tyrosine-tyrosine concentrations. Subjective hunger/fullness was also measured. Total back squat repetitions were greater in CHO (44 (sd 10) repetitions) and PLA (43 (sd 10) repetitions) than WAT (38 (sd 10) repetitions; P < 0·001). Total bench press repetitions were similar between trials (WAT 37 (sd 7) repetitions; CHO 39 (sd 7) repetitions; PLA 38 (sd 7) repetitions; P = 0·130). Performance was similar between CHO and PLA trials. Hunger was suppressed and fullness increased similarly in PLA and CHO, relative to WAT ( P < 0·001). During CHO, plasma glucose was elevated at 45 min ( P < 0·05), whilst serum insulin was elevated ( P < 0·05) and plasma ghrelin suppressed at 45 and 105 min ( P < 0·05). These results suggest that breakfast/pre-exercise nutrition enhances resistance exercise performance via a psychological effect, although a potential mediating role of hunger cannot be discounted.